2015
DOI: 10.3389/fnbeh.2015.00223
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory hole-board test in rats: a new paradigm to study aversion and preferences to odors

Abstract: Odors of biological relevance (e.g., predator odors, sex odors) are known to effectively influence basic survival needs of rodents such as anti-predatory defensiveness and mating behaviors. Research focused on the effects of these odors on rats’ behavior mostly includes multi-trial paradigms where animals experience single odor exposures in subsequent, separated experimental sessions. In the present study, we introduce a modification of the olfactory hole-board test that allows studying the effects of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
(87 reference statements)
2
6
1
Order By: Relevance
“…Additionally, TMT induced a significant increase in immobility, one of the most prominent behavioural effects of TMT 24 , 40 . Surprisingly, exposure to fox urine did not induce overt defensive behaviour in the present experiment, although this has been shown in previous studies of our group 20 , 41 44 and of others 45 – 47 . A potential reason for this may be that the experimental protocol of the present study differed from the one used before.…”
Section: Discussioncontrasting
confidence: 79%
“…Additionally, TMT induced a significant increase in immobility, one of the most prominent behavioural effects of TMT 24 , 40 . Surprisingly, exposure to fox urine did not induce overt defensive behaviour in the present experiment, although this has been shown in previous studies of our group 20 , 41 44 and of others 45 – 47 . A potential reason for this may be that the experimental protocol of the present study differed from the one used before.…”
Section: Discussioncontrasting
confidence: 79%
“…Increased stress reactivity has repeatedly been reported in patients suffering from psychiatric diseases [35,37], and it is suggested that cognitive deficits in schizophrenia may also arise, at least partially, from the increased stress sensitivity and the consequently decreased motivation/attention [31,35,38]. In accordance with the observation that animals with a higher degree of anxiety prefer the peripheral region in open field [4,39], our data revealed that the external side boxes were recognized and preferred by Wisket rats. This points to a higher Table 3 Definitions, abbreviations, means and significances of the different parameters detected in the AMBITUS system, and shown in Fig.…”
Section: (Continued On Next Page)supporting
confidence: 88%
“…This phenomenon seems to be similar to a preference of the peripheral holes compared to the central ones in the hole-board test Wernecke & Fendt, 2015). Since the experiments were performed in dim light without external cues, the learning in the corridor could essentially be considered a form of an egocentric task solved by learning the association between its egocentric body response and the reward (Vorhees & Williams, 2014;Buzsaki & Moser, 2013).…”
Section: Methodological Aspectsmentioning
confidence: 94%